Structural studies of the engrailed homeodomain. - Clarke, N. D. (Cold Spring Harbor Laboratory Press, 1994)
The structure of the Drosophila engrailed homeodomain has been solved by molecular replacement and refined to an R-factor of 19.7% at a resolution of 2.1 A. This structure offers a high-resolution view of an important family of DNA-binding proteins and allows comparison to the structure of the same protein bound to DNA. The most significant difference between the current structure and that of the 2.8-A engrailed-DNA complex is the close packing of an extended strand against the rest of the protein in the unbound protein. Structural features of the protein not previously noted include a "herringbone" packing of 4 aromatic residues in the core of the protein and an extensive network of salt bridges that covers much of the helix 1-helix 2 surface. Other features that may play a role in stabilizing the native state include the interaction of buried carbonyl oxygen atoms with the edge of Phe 49 and a bias toward statistically preferred side-chain dihedral angles. There is substantial disorder at both ends of the 61 amino acid protein. A 51-amino acid variant of engrailed (residues 6-56) was synthesized and shown by CD and thermal denaturation studies to be structurally and thermodynamically similar to the full-length domain.